Never call retreat eaudiobook - Catton, Bruce (The Centennial History of the Civil War, 1990)
Never Call Retreat (Vol 3): Appomattox; the Vicksburg Campaign; the Battle of Atlanta and the March to the Sea; the assassination of Lincoln